Effect of Dry-Wet Cycling on the Mechanical Properties of High-Water Materials. (10th March 2020) - Zhou, X. L.; Liu, C. W.; Liu, Y.; Wang, C.; Ma, Y. J.
Abstract : As a new grouting reinforcement material, high-water materials (HWMs) are being increasingly applied in different fields. This means that the environment in which these HWMs are employed are varied and increasingly complex. The dehydrating and saturation cycle of HWM caused by changes in the environment is referred to as the dry-wet cycle. To explore the influence of the dry-wet cycle on the mechanical properties of HWMs, uniaxial compression tests were performed on specimens with different water-to-cement ratios under different dry-wet cycles. The degradation rate of the peak stress and elastic modulus increased with an increase in the water-to-cement ratio. The failure mode of specimens changed from splitting failure to shear-splitting failure during the dry-wet cycle. The results of scanning electron microscope and X-ray diffraction showed that an HWM with a low water-to-cement ratio is relatively dense; therefore, the carbonization process is slow during dehydration. Raw materials were present after hydration and hardening reaction. Thus, the strength recovery ability is strong in materials with a low water-to-cement ratio during the saturation process. Finally, the experimental results can provide guidance for selecting materials with different water-to-cement ratios and control measures for dry-wet cycle can be determined according to different engineering environments.